Application of multimodal identification technology in the innovative management operation department - Zhu, Yan; Sun, Xiaojiao; Huang, Yuemei; Song, Xiaochong; Liu, Li; Feng, Laide; Zhang, Yujian (Frontiers in Surgery, 2022)
Background The optimization of surgical procedures and the management of surgical quality and safety have become the focus of attention of hospital managers. The application of multimodal identification technology in the innovative management mode of hospital operating department has made remarkable progress. Methods To investigate the effect of the upgraded multimodal identification technology on the innovative management of the operating department, 2280 cases of laparoscopic surgery using traditional surgical management procedures from January to December 2019 before the management upgrade were set as the control group, and 2350 laparoscopic surgeries with the upgraded multimodal identification management process from January to December 2020 were selected as the experimental group. The operating efficiency, material management efficiency, and patient experience and satisfaction of the two groups were investigated and compared. Results Compared with traditional procedures, the upgraded multimodal surgical management system significantly improves the efficiency of laparoscopic surgery and reduces surgical consumption and costs. In addition, the multimodal surgical information identification system significantly improves the surgical experience for patients undergoing laparoscopic surgery. Conclusion Application of multimodal identification technology improves the innovative management of operation department compared with traditional surgery management procedure.